Electric-field induced microdynamics of charged rods - Kang, Kyongok (Frontiers in Physics, 2014)
Electric-field induced phase/state transitions are observed in AC electric fields with small amplitudes and low frequencies in suspensions of charged fibrous viruses (fd), which are model systems for highly charged rod-like colloids. Texture- and particle-dynamics in these field-induced states, and on crossing transition lines, are explored by image time-correlation and dynamic light scattering, respectively. At relatively low frequencies, starting from a system within the isotropic-nematic coexistence region, a transition from a nematic to a chiral nematic is observed, as well as a dynamical state where nematic domains melt and reform. These transitions are preliminary due to field-induced dissociation/association of condensed ions. At higher frequencies a uniform state is formed that is stabilized by hydrodynamic interactions through field-induced electro-osmotic flow where the rods align along the field direction. There is a point in the field-amplitude versus frequency plane where various transition lines meet. This point can be identified as a “non-equilibrium critical point”, in the sense that a length scale and a time scale diverge on approach of that point. The microscopic dynamics exhibits discontinuities on crossing transition lines that were identified independently by means of image and signal correlation spectroscopy.